Transcriptome Analysis of the Breast Muscle of Xichuan Black-Bone Chickens Under Tyrosine Supplementation Revealed the Mechanism of Tyrosine-Induced Melanin Deposition - Li, Donghua; Wang, Xinlei; Fu, Yawei; Zhang, Chenxi; Cao, Yanfang; Wang, Jie; Zhang, Yanhua; Li, Yuanfang; Chen, Yi; Li, Zhuanjian; Li, Wenting; Jiang, Ruirui; et al. (Frontiers in Genetics, 2019)
The Xichuan black-bone chicken, which is a rare local chicken species in China, is an important genetic resource of black-bone chickens. Tyrosine can affect melanin production, but the molecular mechanism underlying tyrosine-induced melanin deposition in Xichuan black-bone chickens is poorly understood. Here, the blackness degree and melanin content of the breast muscle of Xichuan black-bone chickens fed a basic diet with five levels of added tyrosine (i.e., 0.2%, 0.4%, 0.6%, 0.8% and 1.0%; these groups were denoted test groups I-V, respectively) were assessed, and the results showed that 0.8% tyrosine was the optimal level of added tyrosine. Moreover, the effects of tyrosine supplementation on the proliferation and tyrosinase content of melanocytes in Xichuan black-bone chickens were evaluated. The results revealed a dose-dependent relationship between tyrosine supplementation and melanocyte proliferation. In addition, 417 differentially expressed genes (DEGs), including 160 upregulated genes and 257 downregulated genes, were identified in a comparative analysis of the transcriptome profiles constructed using the pooled total RNA from breast muscle tissues of the control group and test group IV, respectively (fold change ≥ 2.0, P < 0.05). These DEGs were mainly involved in melanogenesis, the calcium signaling pathway, the Wnt signaling pathway, the mTOR signaling pathway, and vascular smooth muscle contraction. The pathway analysis of the DEGs identified some key genes associated with pigmentation, such as DCT and EDNRB2. In summary, the melanin content of breast muscle could be markedly enhanced by adding an appropriate amount of tyrosine to the diet of Xichuan black-bone chickens, and the EDNRB2-mediated molecular regulatory network could play a key role in the biological process of tyrosine-induced melanin deposition. These results have deepened the understanding of the molecular regulatory mechanism of melanin deposition in black-bone chickens and provide a basis for the regulation of nutrition and genetic breeding associated with melanin deposition in Xichuan black-bone chickens.